Health Promotion to Increase Knowledge about Puberty in Boys - Denys Putra Alim; Erik Jaya Gunawan; Yohan Christian Suisan; Raden Roro Shinta Arisanti; Ihyan Amri (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Puberty is a normal developmental process in which a child develops into a biologically and/or sexually mature adult. Even though puberty is a natural event, it is not uncommon for children to be confused or worried about puberty. Therefore, using the Participatory Action Research Method, this community service aims to increase knowledge about puberty in boys in the Sambikerep sub-district, Surabaya. The activities include health promotion, education, and free circumcision for the children by surgeons and medical students from the School of Medicine, Universitas Ciputra Surabaya. Statistical analysis of knowledge before and after health promotion used the Wilcoxon test in SPSS version 26 with a significance limit of p < 0.05. The overall community service activities ran quite smoothly; there were 24 children who took part, with the number of children getting a pre-test score < 75 points as high as 29.2%. However, no children got a post-test score of < 75 points after the health promotion. The median score of knowledge about puberty before and after health promotion was 75 (12.5–100) and 100 (87.5–100) points, respectively (p-value <0.001). Through this community service, health promotion and education about puberty must be continuously provided to pre-pubertal boys so that they have a good understanding of puberty and make healthy decisions related to their sexual and emotional health.